2006
DOI: 10.1158/0008-5472.can-05-3726
|View full text |Cite
|
Sign up to set email alerts
|

The Synovial Sarcoma–Associated SS18-SSX2 Fusion Protein Induces Epigenetic Gene (De)Regulation

Abstract: Fusion of the SS18 and either one of the SSX genes is a hallmark of human synovial sarcoma. The SS18 and SSX genes encode nuclear proteins that exhibit opposite transcriptional activities. The SS18 protein functions as a transcriptional coactivator and is associated with the SWI/SNF complex, whereas the SSX proteins function as transcriptional corepressors and are associated with the polycomb complex. The domains involved in these opposite transcriptional activities are retained in the SS18-SSX fusion proteins… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
75
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(78 citation statements)
references
References 52 publications
3
75
0
Order By: Relevance
“…Due to the heterogeneity of sarcoma, >100 distinct subtypes have been described to date, with new subtypes frequently reported (4). Synovial sarcoma, a soft-tissue tumor, is characterized by a reciprocal t(X;18) translocation, in which the SS18 gene on chromosome 18 fuses with the SSX1, SSX2 or, less commonly, SSX4 gene on the X chromosome (5,6). Ewing's sarcoma has a relatively simple genetic signature, consisting of a t(11;22) translocation (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…Due to the heterogeneity of sarcoma, >100 distinct subtypes have been described to date, with new subtypes frequently reported (4). Synovial sarcoma, a soft-tissue tumor, is characterized by a reciprocal t(X;18) translocation, in which the SS18 gene on chromosome 18 fuses with the SSX1, SSX2 or, less commonly, SSX4 gene on the X chromosome (5,6). Ewing's sarcoma has a relatively simple genetic signature, consisting of a t(11;22) translocation (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…The QPGY domain is a transcriptional coactivation domain and mediates multimerization of the SS18 protein (Brett et al, 1997;Thaete et al, 1999;Perani et al, 2003). Together, these findings indicate that the SS18 protein acts as transcriptional co-activator through chromatin modification mechanisms (de Bruijn et al, 2006).…”
Section: Introductionmentioning
confidence: 80%
“…The main body of the SS18 protein, including the SNH domain, is fused to the highly polar C-terminal SSX tail, including the SSX-divergent (SXXDDs) and SSXRDs. This fusion has been associated with neoplastic transformation (Nagai et al, 2001) and changes in the epigenetic makeup of target genes (de Bruijn et al, 2006). Another recent study indicated that the SS18-SSX1 and SS18-SSX2 fusion proteins interact preferentially with the transcription factors Snail and Slug, respectively (Saito et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This could In synovial sarcoma, in vitro studies have found that the SS18-SSX oncogene induces IGF2 expression which seems critical to convey tumorigenic properties. [48][49][50] IGF2 expression was associated with both the ÀSSX1 and ÀSSX2 translocation subtypes. 48 In this study, we present evidence that in primary synovial sarcoma tumor specimens, IGF2 is highly expressed at the protein level, supporting translational relevance to patients of these experimental findings, and attempts to target this pathway in patients using IGF signaling inhibitors.…”
Section: Discussionmentioning
confidence: 98%